Clinical Application of Indocyanine Green Fluorescence Imaging in the Resection of Hepatoblastoma: A Single Institution's Experiences - Shen, Yuanchao; Zheng, Manna; Li, Jiahao; Tan, Tianbao; Yang, Jiliang; Pan, Jing; Hu, Chao; Zou, Yan; Yang, Tianyou (Frontiers in Surgery, 2022)
Purpose Indocyanine green (ICG) fluorescene imaging is becoming increasing popular in adult oncologic surgery, but remains relatively uncommon in pediatric oncologic surgery. Herein, we report our experience with the use of ICG fluorescene imaging in the resection of hepatoblastoma (HB). Patients and Methods Hepatoblastoma patients who underwent liver resection with ICG fluorescene imaging between January 2020 and March 2021 were included in this study. Patients’ demographic data, clinical information, and detailed information of the use of ICG fluorescene imaging were retrospectively reviewed. Results Sixteen HB patients underwent ICG fluorescence imaging-guided liver resection. There were 11 males and 5 females, age ranged from 8 to 134 months. The initial alpha-fetoprotein (AFP) ranged from 436 ng/ml to 528390 ng/ml. There were 1 pre-treatment extent of tumor (PRETEXT) stage I, 9 stage II, 4 stage III, and 2 stage IV. Three patients underwent up-front hepatectomy, thirteen patients received 2 - 8 cycles of platinum-based neoadjuvant chemotherapy and underwent delayed hepatectomy. ICG (0.5mg/kg) was given intravenously 48 – 72 hours prior to surgery. The operative time ranged from 180 minutes to 400 minutes. All patients achieved negative surgical margins. In two patients, ICG identify additional lesions which were no detected in preoperative imaging. Conclusion ICG fluorescence imaging is useful in the resection of HB, and may detect small lesions not showed in preoperative imaging.